Condensation Characteristics of Superhydrophobic Surface at Different Working Conditions - Gu Guiyu; Sheng Wei; Zheng Haikun; Hao Xiaoru; Wang Ruirui (Zhileng xuebao)
Superhydrophobic surfaces can reduce the attachment of droplets, reduce the increase of thermal resistance caused by the existence of droplets, and thereby improve the efficiency of air conditioning, power generation, and seawater desalination systems. This study experimentally investigates the growth characteristics of condensate droplets on a superhydrophobic surface under different cold surface temperatures (2–8 ℃), relative humidity values (40%–80%), and inclination angles (0°–90°) and analyzes the effects of different working conditions on superhydrophobic-surface condensation. The results show that with a decrease in the cold surface temperature, the average droplet growth radius and surface droplet coverage gradually increase. The lower the cold surface temperature, the faster the droplet growth rate. The droplets on the superhydrophobic surface grow faster under high humidity, while the droplet growth radius under low humidity will exceed that under medium and high humidity after sufficient time. The droplet coverage on the cold surface under low and medium humidity conditions is considerably less than that under high humidity conditions. The critical sweep radius of droplets decreases gradually with an increase in inclination angle, and the droplet coverage on the vertical surface decreases by 42% compared with that on the horizontal surface.